Prognostic factors of refractory epilepsy in children - Ramzi Ramzi; Yati Soenarto; Sunartini Sunartini; M Hakimi (Indonesian Pediatric Society, 2008)
Background Epilepsy is one of the most common pediatricneurological disorders. Twenty percent of patients will developrefractory epilepsy. Early identification of refractory epilepsy willbe helpful to conduct adequate counseling and selecting patientswho need more intensive investigation and treatment.Objective To identify the clinical characteristics and other factorsthat are related to refractory epilepsy in children.Methods We conducted a case control study in patients of two to18 years old with epilepsy that admitted to Dr. Sardjito Hospital.There were 4 7 children with refractory epilepsy compared with122 subjects who have been one year free of seizure.Results Strong association had been noted between refractoryand several clinical factors: early onset of seizure, high initialseizure frequency, neonatal asphyxia, symptomatic etiology, statusepilepticus, abnormal neurodevelopmental status, and earlybreakthrough seizures after treatment initiation. On multivariateanalysis, more than 20 seizures prior to treatment initiation (OR3.40, 95% CI 1.03 to 11.3), and more than three seizures in thesubsequent six month after treatment initiation (OR 16.02, 95%CI 4.98 to 51.5) were independent prognostic factors related torefractory epilepsy.Conclusion Children who present high frequency seizures atonset and more than 3 breakthrough seizures subsequent to sixmonth after treatment have risks of developing refractory epilepsy.